Patterns of Change in Collaboration Are Associated with Baseline Characteristics and Predict Outcome and Dropout Rates in Treatment of Multi-Problem Families. A Validation Study - Bachler, Egon; Fruehmann, Alexander; Bachler, Herbert; Aas, Benjamin; Nickel, Marius; Schiepek, Guenter K. (Frontiers in Psychology, 2017)
OBJECTIVE: The present study validates the Multiproblem Family (MPF)-Collaboration Scale), which measures the development of goal-directed collaboration of patients in the treatment of families with multiple problems (MPF) and its relation to drop-out rates and treatment outcome. METHOD: Naturalistic study of symptom and competence-related changes in children of ages 4-18 and their caregivers. SETTING: Integrative, structural outreach family therapy. MEASURES: The data of 5 different groups of goal directed collaboration (deteriorating collaboration, stable low collaboration, stable medium collaboration, stable high collaboration, improving collaboration) were analyzed in their relation to treatment expectation, individual therapeutic goals, family adversity index, severity of problems and global assesment of functioning of caregiver, child and relational aspects. RESULTS: From N = 810 families, 20% displayed stable high collaboration (n = 162) and 21% had a pattern of improving collaboration. These families with stable high or improving collaboration had significant more progress throughout therapy in terms of treatment outcome expectancy (d = 0.96; r = 0.43), achieving individual therapeutic goals (d = 1.17; r = 0.50), family adversities (d = 0.55; r = 0.26), and severity of psychiatric symptoms (d = 0.31; r = 0.15). Furthermore, families with stable high or improving collaboration maintained longer treatments and had a bigger chance of finishing the therapy as planned. The odds of having a stable low or deteriorating collaboration throughout treatment were significantly higher for subjects that started treatment with low treatment expectation or high family-related adversities. CONCLUSIONS: The positive outcomes of homebased interventions for multi-problem families are closely related to “stable high” and an “improving” collaboration as measured with the MPF-Collaboration Scale. Patients falling into these groups have a high treatment outcome expectancy and reduce psychological stress. For therapeutic interventions with multiproblem families it seems beneficial to maintain a stable high collaboration or help the collaboration, e.g. by fostering treatment expectation.